Completing the Legislation of Crime in Vietnam's Current Criminal Law - Cam, Le (VNU Journal of Science: Legal Studies; Vol 34 No 1, 2018)
The article analyzes the situation and points out some shortcomings of the legislation of crime in the current Criminal Code (the Penal Code 2015) (12 articles from Article 8 to Article 19) as well as proposes a solution to continue improving Vietnam Criminal Law in the future with a  legislative model including: 1) Keep stable 03 articles (13, 18-19); 2) Transfer 01 article (Article 13 Penal Code 2015) to the new Independent Chapter on Criminal Responsibility (needs to be added to the Penal Code in the future) accordingly; 3) Add 11 more new articles to complete the legislation of crime. Keywords Legislation, crime, Penal Code 2015, Criminal Law in the future, Legislative Model References [1] Lê Văn Cảm, Nguyễn Thị Lan. Nghiên cứu các luận điểm từ lý luận về lập pháp hình sự trong Nhà nước pháp quyền. Tạp chí Khoa học - Chuyên san Luật học, số 3/2017. [2] Hiến pháp Việt Nam năm 2013. [3] Bộ luật hình sự Việt Nam năm 2015 (sửa đổi, bổ sung năm 2017). [4] Lê Văn Cảm, Luật hình sự Việt Nam và sự nghiệp xây dựng Nhà nước pháp quyền: Một số vấn đề hoàn thiện các quy phạm của Phần chung. Tạp chí Toà án nhân dân, số 9/1997.